Intestinal flora and linear growth in children - He, Pingsihua; Shen, Xingyuan; Guo, Sheng (Frontiers in Pediatrics, 2023)
The gut microbiota plays a critical role in human growth and development as well as the regulation of human pathophysiological processes. According to research, the gut microbiota controls the host's growth and development in areas such as nutrition, metabolism, endocrine hormones, and immune modulation. The human gut microbiota has an important role in child and adolescent growth, especially when nutritional conditions are poor. In this review, we focus on recent findings about the gut microbiota's influence on child growth, including the relationship between the gut microbiota and linear growth during pregnancy, infancy, childhood, and adolescence. Furthermore, we also review some mechanisms by which intestinal flora influence the host's linear growth. Although the data supports a link between intestinal flora and linear development in children, our review has limitations that prohibit us from fully verifying the causal relationship between gut flora and linear development in children. Improving the gut microbiota, in conjunction with renutrition techniques, has the potential to ameliorate the growth and development impairments currently associated with chronic illness and malnutrition in children.